Building An Ontology-Based Multilingual Lexicon For Word Sense Disambiguation In Machine Translation. - Lim, Lian-Tze; Tang, Enya Kong (2004)
Word sense disambiguation (WSD) requires the establishment of a list of the different meanings of words. WSD efforts in machine translation require) in addition) the equivalent translation words in target languages.